Induction of Multichotomous Branching by CLAVATA Peptide in Marchantia polymorpha - Hirakawa, Yuki; Fujimoto, Toko; Ishida, Sakiko; Uchida, Naoyuki; Sawa, Shinichiro; Kiyosue, Tomohiro; Ishizaki, Kimitsune; Nishihama, Ryuichi; Kohchi, Takayuki; Bowman, John L. (Current biology, 2020)
A key innovation in land plants was the evolution of meristems with stem cells possessing multiple cutting faces (division planes) from which three-dimensional growth is derived in both haploid (gametophyte) and diploid (sporophyte) generations [1–3]. Within each meristem exists a pool of stem cells that must be maintained at a relatively constant size for development to occur appropriately [4–6]. In flowering plants, stem cells of the diploid generation are maintained by CLAVATA3/EMBRYO SURROUNDING REGION-related (CLE) peptide signaling [7, 8]. In the liverwort Marchantia polymorpha, the haploid body undergoes dichotomous branching, an ancestral characteristic of growth derived from the meristem, in which two equivalent body axes are developed via stem cell division, regulated by unknown molecular mechanisms. We show here that in M. polymorpha, treatment with MpCLE2/CLAVATA3 (CLV3) peptide resulted in the accumulation of undifferentiated cells, marked by MpYUC2 expression, in the apical meristem. Removal of MpCLE2 peptide resulted in multichotomous branching from the accumulated cells. Genetic analysis demonstrated that the CLAVATA1 (MpCLV1) receptor, but not the WUSCHEL-related HOMEOBOX (MpWOX) transcription factor, is responsible for MpCLE2 peptide signaling. In the apical meristem, MpCLV1 was expressed broadly in the central region, including the MpYUC2-positive area, whereas MpCLE2 was expressed in a largely complementary manner compared to MpYUC2, suggesting MpCLE2 mediates local cell-to-cell communication. CLV3/CLE peptide, a negative regulator of diploid stem cells in flowering plants, acts as a haploid stem cell-promoting signal in M. polymorpha, implicating a critical role for this pathway in the evolution of body plan in land plants. [Display omitted] •MpCLE2 peptide influences meristem activity in the Marchantia polymorpha gametophyte•Multiple branches can be induced by temporal treatment with MpCLE2 peptide•The meristematic cell population is positively regulated by MpCLE2 signaling•The MpCLV1 receptor, but not MpWOX transcription factor, acts in MpCLE2 signaling Hirakawa et al. demonstrate that a plant peptide, MpCLE2/CLV3, functions as a stem cell-promoting hormone in the haploid body of the liverwort Marchantia polymorpha. Combined with prior studies, this finding provides a molecular link between apical meristems in the haploid and diploid generations of land plants.